School money trials : the legal pursuit of educational adequacy - West, Martin R.; Peterson, Paul E. (Brookings Institution Press, 2007)
Adequacy lawsuits have, with little fanfare, emerged as a major alternative strategy in the pursuit of improved public education in the United States. Plaintiffs allege insufficient resources to provide students with the quality of education promised in their state's constitution, hoping the courts will step in and order the state to increase funding levels. Since 1985, more than thirty states have faced such suits. How pervasive--and effective--is this trend? What are its ramifications, in local school districts and on a broader scale? This important new book addresses those questions. In Sch.
Keywords: Educational equalization -- Law and legislation -- United States.; Educational accountability -- Law and legislation -- United States.; Discrimination in education -- Law and legislation -- United States.; Education -- Finance -- Law and legislation -- United States -- States.; Education -- United States -- Finance.; LAW -- Administrative Law & Regulatory Practice.; EDUCATION -- Educational Policy & Reform -- General.; Discrimination in education -- Law and legislation; Education -- Finance; Education -- Finance -- Law and legislation -- U.S. states; Educational accountability -- Law and legislation; Educational equalization -- Law and legislation; United States